PRANATA MANGSA DAN BUDAYA KEARIFAN LINGKUNGAN - Sobirin, Supardiyono (Jurnal Budaya Nusantara, 2018)
Pranata mangsa is a traditional calendar about the rules of the season which has long been known primarily bythe farming community in Java. This calendar is based on pseudo-circulation of the sun, which in the past was a reliableguide for farmers to schedule farming in the rice fields. Along with the progress of civilization of life, understanding of pranata mangsa has faded a lot, among other things because of environmental changes due to population growth, land use change, climate anomalies, and modernization of life. Although pranata mangsa has experienced many deviations, it is assumed that it can still be saved as a very wise and valuable ancestral heritage. One of the benefits is as a cultural aid in preserving the environment, and as a basis for understanding the current season's forecasting technology. A hope that pranata mangsa culture can be revived, namely if the concept of development is carried out on the basis of consistent ecological sustainability, with integrated support in the form of political will, educational will, and cultural will, and integrating traditional wisdom of pranata mangsa with modern technology.